Case Report: Multi-targeted therapy in the treatment of severe toxic epidermal necrolysis - Kwong, Elaine Yi Lee; Kuok, Manson Chon In; Lam, King Fai; Chan, Winnie Kwai Yu (Frontiers in Pediatrics, 2024)
We reported a 10-year-old child who suffered from severe toxic epidermal necrolysis (TEN) triggered by trimethoprim-sulfamethoxazole and managed successfully with multi-targeted therapy.He was jointly managed by the paediatric intensivist, dermatologist, otolaryngologist, urologist, wound nurse, pain management specialist, dietitian and clinical psychologist. Systemic intravenous immunoglobulin (IVIG) and pulsed-dose methylprednisolone were initiated after admission. Oral cyclosporin A was added in the early stage of the disease in view of severe ocular involvement with progressive inflammation of bilateral upper and lower eyelids, presence of pseudomembrane, diffuse conjunctival injection and progression of central epithelial defects in bilateral eyes. He underwent amniotic membrane transplantation. Subcutaneous injection of etanercept was added on the treatment therapy to allow rapid tapering of steroid. Finally, the disease progression was halted with re-epithelisation on day 13. He experienced no side effects from the multi-targeted therapy and recovered well without clinical sequelae.